2012
DOI: 10.1111/j.1365-2591.2012.02068.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stem cell properties of cells isolated from normal and inflamed dental pulps

Abstract: The morphology, proliferation rate and differentiation potential of DPSC-I were similar to the observed in DPSC-N, thus demonstrating that the inflammatory process did not affect the stem cell properties that were assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 31 publications
7
40
1
2
Order By: Relevance
“…STRO-1 has been previously observed in pulp tissues and is regarded as a marker for stromal stem cells, recognizing the trypsin-insensitive epitope on perivascular cells (4). In the majority of previous studies, STRO-1 expression has been observed in DPSCs, with an expression level ranging between 0.46 and 26.14% (4,14,17). CD146 is a stem cell marker identified in adult bone marrow and dental pulp tissue, associated with blood vessels (18).…”
Section: Discussionmentioning
confidence: 99%
“…STRO-1 has been previously observed in pulp tissues and is regarded as a marker for stromal stem cells, recognizing the trypsin-insensitive epitope on perivascular cells (4). In the majority of previous studies, STRO-1 expression has been observed in DPSCs, with an expression level ranging between 0.46 and 26.14% (4,14,17). CD146 is a stem cell marker identified in adult bone marrow and dental pulp tissue, associated with blood vessels (18).…”
Section: Discussionmentioning
confidence: 99%
“…This ablative approach is based on the generally accepted belief that once infection reaches the pulp, the infected and locally inflamed neurovascular structure may be irreversibly damaged with limited capability for repair. Recent studies reported that a subset of MSCs derived from inflamed human pulps preserve the full capability of proliferation and multipotent differentiation as compared with those from healthy pulps (DPSCs; Alongi et al 2010;Wang et al 2010;Pereira et al 2012), suggesting that inflamed pulp may not be completely depleted of progenitor/stem cells but can be repaired.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have compared the cells from normal and inflamed human dental pulps regarding the presence of stem cells, their proliferation and differentiation potentials [27][28][29][30]. Diseased pulp contains viable cells with the potential for ex vivo expansion and proliferation, a similar percentage of STRO-1-positive cells and ex vivo odonto-osteogenic differentiation capacity.…”
Section: Dentin-pulp Tissue Regeneration With Inflamed Pulp Tissuementioning
confidence: 99%